The analysis of the varietal structure of spring barley in the Rostov region - S. A. Raeva; V. P. Perepechaeva (Зерновое хозяйство России, 2018)
The article presents the analysis of the varietal structure of spring barley sowings. There are 30 varieties of spring barley cultivated in the Rostov region, among which there are five new varieties occupying 6.9% of the general sowing area. The varieties which have been grown for 11-15 years are the most spread and occupy 32% of the sowing area. There is a tendency to increase the sowing area of the varieties which have been grown for less than 5 years or for 16-20 years. The varieties grown for more than 20 years have a large proportion (29.1%) in the general sowing area of spring barley. It is due to conservatism of grain producers, who prefer old, proven varieties. The improvement of the varietal structure of the sowing areas can become a reserve of the grain production increase in the Rostov region.